Kompetensi Kolaborasi sebagai Pendorong Penciptaan Pengetahuan, Inovasi, dan Kinerja Pemasaran pada Usaha Kecil dan Mengengah - Purnama, Annur Wulan; Tjahjono, Heru Kurnianto; Widowati PA., Retno (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Employee performance often declines when leadership lacks moral integrity and fails to inspire internal motivation. This study examines the influence of ethical leadership on employee motivation and performance. It contributes to leadership and organizational behavior literature by clarifying the mediating role of intrinsic motivation in the ethical leadership–performance relationship. Using Structural Equation Modeling (SEM) with AMOS, the results show that ethical leadership significantly enhances intrinsic motivation, which subsequently improves performance, while its direct effect on performance is insignificant. These findings advance understanding of how ethical leadership operates through internal psychological mechanisms rather than direct behavioral influence. Strengthening ethical leadership practices and nurturing intrinsic motivation can enhance organizational performance and sustain a positive work climate.